When Land Was Cheap, and Labor Dear: James Madison's ‘Address to the Albemarle Agricultural Society’ and the Problem of Southern Agricultural Reform - Nelson, Lynn A. (History compass, 2008)
James Madison's 1818 Address to the Albemarle Agricultural Society offers new insight into the diverse historiography of agricultural reform in the American South. Madison described a planet with limited resources, accused Virginia farmers of wasting what little they had, and offered suggestions for ways to intensify cultivation. Many scholars have analyzed the southern agricultural reform crusade, but differ widely on whether it was successful, and the reasons why. Madison tried to balance high farming with southern independence. Southern farming could not imitate modern agriculture from England and the Northeastern states because of the region's ecological distinctiveness. Madison was reluctant to risk tested adaptations by importing to crops, animals, and fertilizers. Southern farmers reflected his ecological conservatism, and the movement for reform stalled.